2010
DOI: 10.1002/app.31832
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water‐soluble polymers on rheology of microfibrillar cellulose suspension and dynamic mechanical properties of paper sheet

Abstract: Rheological properties of fiber/polymer suspensions and dynamic mechanical analysis (DMA) of paper sheets containing the same polymers were measured. Correlations between viscoelastic properties of suspensions and strength of paper sheet are presented. Rheological properties of suspensions of microfibrillar cellulose (MFC) and a set of water soluble polymers were measured. Rheological properties of these complex fluids vary considerably depending on the added polymer. A suspension of fiber and carboxymethyl ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…2b). This is in agreement with our earlier results (Vesterinen et al 2010a), which showed that cationic polyelectrolytes strengthened MFC suspension while maintaining gel-like behavior. By contrast, the amphiphilic cationic PSMA13Q decreased the storage and loss modulus at a concentration of 0.5 wt% (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…2b). This is in agreement with our earlier results (Vesterinen et al 2010a), which showed that cationic polyelectrolytes strengthened MFC suspension while maintaining gel-like behavior. By contrast, the amphiphilic cationic PSMA13Q decreased the storage and loss modulus at a concentration of 0.5 wt% (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Different polymers have been mixed with MFC/ water suspension to affect the rheological properties of the suspensions (Lowys et al 2001;Vesterinen et al 2010a;Vesterinen and Seppälä 2008) or to the aggregation of the fibers (Myllytie et al 2009), but the results have not been combined. Our group (Vesterinen et al 2010a) studied the addition of carboxymethylcellulose, cationic polyacrylamide, and cationic starch to MFC suspensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related effects have been widely reported (e.g. by Guo and Ding 2006;Vesterinen et al 2010;Boluk et al 2012;Hu et al 2014;Lu et al 2014c;Ahn and Song 2016;Oguzlu et al 2016).…”
Section: Bridging Effects Of Nanocellulosementioning
confidence: 77%
“…Even at low concentrations, the CNF suspensions exhibit quite a complex rheological behaviour; they are shear-thinning, at least at not too high shear rates, and elastic in nature; compare, for example, [5,[26][27][28]. Both the shear viscosity and the viscoelastic parameters of the CNF suspensions are affected by additives like salts, carboxymethyl cellulose, cationic starch, and polymethacrylates [29,30]. The CNF suspensions, with a fibril content exceeding the percolation threshold, exhibit a gel-like behaviour with a yield stress, a storage modulus greater than the loss modulus, and the moduli being rather insensitive to changes in the measuring frequency, for example, [5,26], and to moderate changes in temperature, up to 80 ∘ C [5,31].…”
Section: Introductionmentioning
confidence: 99%